2017
DOI: 10.1080/15376516.2017.1366609
|View full text |Cite
|
Sign up to set email alerts
|

Effect of size and shape on toxicity of zinc oxide (ZnO) nanomaterials in human peripheral blood lymphocytes

Abstract: The multi-industrial applications of zinc oxide nanomaterials (ZnO NMs) lead to increasing exposure to humans. Though the ZnO nanoparticles (NPs) toxicity had been evaluated previously, toxicity of other forms of ZnO nanomaterials has not been evaluated. In this study, cytotoxicity and genotoxicity of four different types of ZnO NMs were evaluated using human peripheral blood lymphocytes (HPBL). In addition, the effect of anti-oxidants on ZnO NMs induced toxicity was also evaluated. Our results suggest that, s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
31
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 41 publications
(34 citation statements)
references
References 44 publications
2
31
0
1
Order By: Relevance
“…A report by Ahamed et al (2011) on Ni ferrite NPs showed ROS-mediated oxidative stress, which further induced apoptosis in A549 cells. Furthermore, the apoptotic response documented in the current study is supported by an investigation of NiO-NPs when exposed to HepG2 cells (Ahamed, Ali, Alhadlaq, & Akhtar, 2013 Shalini et al, 2018;Zarei et al, 2018). NiO-NP-treated HPBL cells showed a dose-response effect with different NiO-NP doses with comet and CBMN assays.…”
Section: Induction Of Reactive Oxygen Species After Nio Nanoparticlsupporting
confidence: 74%
“…A report by Ahamed et al (2011) on Ni ferrite NPs showed ROS-mediated oxidative stress, which further induced apoptosis in A549 cells. Furthermore, the apoptotic response documented in the current study is supported by an investigation of NiO-NPs when exposed to HepG2 cells (Ahamed, Ali, Alhadlaq, & Akhtar, 2013 Shalini et al, 2018;Zarei et al, 2018). NiO-NP-treated HPBL cells showed a dose-response effect with different NiO-NP doses with comet and CBMN assays.…”
Section: Induction Of Reactive Oxygen Species After Nio Nanoparticlsupporting
confidence: 74%
“…When applied to HepG2 cells (cancer cell line) and HUVECs (normal cells), these NMs showed a similar trend that ZnO NRs and ZnO Mini‐NRs were significantly more cytotoxic compared with a/c‐ZnO MS (Figure and Supplemental Figure S3). This could be attributed by the unique structures of a/c‐ZnO MS, which contributed to their larger sizes (Table ), and previous studies have shown that the toxicity of ZnO particles could be decreased with the increase of particle sizes (Shalini, Senthilkumar, & Rajaguru, ; Uski et al, ; Yin, Casey, McCall, & Fenech, ). Exposure to a‐ZnO MS and c‐ZnO MS induced cytotoxicity to a similar extent.…”
Section: Discussionmentioning
confidence: 91%
“…Due to ZnO NPs high UV light absorption and reflective properties, ZnO NPs provide protection from ultraviolet radiation A and B and hence justifies their use in sunscreens and paints (Senapati et al 2017). In its original form, ZnO is a low toxic material commonly present in food and added as a nutritional supplement, but at the nano-scale, its increased chemical reactivity, oxidation resistance and UV filtering efficiency are the reason it has found increased commercial use (Shalini et al 2017). Despite their widespread usage in consumer products, the mechanism for their cytotoxicity is not well known and the in vitro cytotoxic effects of ZnO NPs, therefore, must be fully understood.…”
Section: Introductionmentioning
confidence: 99%
“…The physiochemical characteristics of ZnO NPs, surface reactivity, particle number, dissolution, chemical composition etc. play an important part in its toxicological response, specifically ZnO NPs toxicity has been attributed to the release of free ionic zinc, that induces free ROS which, results in subsequent cellular damage and finally cell death (Shalini et al 2017). ZnO NPs mediated cytotoxicity has been noted to be dependent on their surface properties (Saptarshi et al 2013) and their cellular uptake has been shown to occur via endocytosis (Kao et al 2012, Jeong et al 2013, Yan et al 2014.…”
Section: Introductionmentioning
confidence: 99%